Fostering the relationship between home and school : a case study of a senior secondary school in the Gambia - Babatunde, Adeshina (2011)
The study examines the extent to which the relationship between home and school affects students’ academic achievements. A senior secondary school in The Gambia was chosen for this study. The focus of the research was to identify and describe intentionally designed programs and practices that foster the involvement of home in school activities and its important outcomes for the stakeholders (home and school). A qualitative method using semi-structured interviews was used to collect the data from the school principal, four English language teachers and ten parents in order to explore the nature and the degree of support they provide for students. The data was analyzed by the researcher using content analysis method. Relevant literature gathered from various academic sources and the work of previous researchers provided an important theoretical framework for this study. Findings from the data collected identify motivation, communication, collaboration, shared leadership, flexibility and transparency as important factors in a successful home-school relationship. The study proffers recommendations on fostering the relationship between home and school through the provision of systematic support for parents via seminars and workshops. The inputs of home and school should also be honored in order to pave the way for greater participation and effective support for student achievement. Checks and balances also should be in place so that involvement does no turn to interference.